Germaborenes: Borylene Transfer Agents for the Synthesis of Iminoboranes. Issue 6 (23rd December 2020) - Raiser, Dominik; Schubert, Hartmut; Bettinger, Holger F.; Wesemann, Lars
Abstract: Halide and phenyl substituted germaborenes were shown to react with azides at room temperature and transfer a borylene moiety to give iminoboranes. This iminoborane synthesis based on a borylene transfer route was investigated computationally in the case of the phenyl substituted germaborene. Abstract : Germaborenes act as borylene transfer agents to azides in the synthesis of iminoboranes.